Spotlight On - Ambrose, Ann Peele (Cengage Learning, Inc, 2007)
The Spotlight On... series allows you to mix and match dedicated texts to suit your specific classroom needs. These easy-to-follow, fun and visual books keep learners engaged and interested in what they are learning. Users are introduced to new concepts in the lessons and then gain valuable hands-on experience using these skills in a variety of cross-curricular scenarios